Recent trends in future proof fiber access passive networks: GPON and WDM PON - Satyanarayana, K; Abhinov, Balagoni (2014 International Conference on Recent Trends in Information Technology, 2014)
Fiber to the Home (FTTH) is broadly acknowledged as the optimal solution for meeting the current and future broadband requirements. FTTH involves the installation of optical fiber network from a central service provider to individual users. An innovative technology for FTTH implementation is Passive Optical Network (PON), which provides unprecedented bandwidth. The attributes of modern passive optical network (PON) such as high reliability, low cost, passive functionality are mainly responsible for the proliferation of optical fiber access. The recent trends in fiber access passive optical networks include Ethernet Passive Optical Network (EPON), Gigabit Passive Optical Network (GPON) and Wavelength Division Multiplexing Passive Optical Network (WDM PON). This paper focuses on PON such as GPON and next generation WDM PON. This paper discusses key technological aspects, and challenges of GPON, and next generation WDM PON and aims to provide insights to a reader by doing a comparative study of the two fiber access passive networks on the basis of cost, capacity and flexibility.